Bones in space: taphonomy and the pre-and post-depositional movement of bones - Alvarez, María Clara; Gonzalez, Mariela Edith; Scheifler, Nahuel Alberto; Kaufmann, Cristian Ariel; Gutierrez, Maria Amelia; Massigoge, Agustina; Rafuse, Daniel Joseph (International Council for Archaeozoology, 2014)
Using the same space and resources by humans and carnivores often leads to the formation of complex faunal assemblages, in which the anatomical and taxonomic composition responds to the combined action of both agents. The aim of this paper is to present the results of actualistic research on the action of carnivores from the Argentina Pampean region and their implications for the regional archaeological record. Our current investigations involve naturalistic studies, developed in different environments (hills, lakes, coast, plains, and river valleys) and controlled experiments with captive predators. However, in this opportunity we will focus on the naturalistic information. In the Pampas, small carnivores (under 25 kg) predominate, such as the pampas fox, Geoffrey?s cat, lesser grison, and domestic dog. The naturalistic record consists of isolated bones, bone concentrations, carcasses and feces deposited by carnivores, being small mammals and birds the prevalent prey. The high percentage of marks registered in the hill environment (ca. 44%) suggests that in this sector of the landscape, carnivores played an important role in bone accumulation. As for the other environments, the frequencies of marks are significantly lower (between 10 and 15%). The archaeological record from corresponding environments in the region shows evidence of carnivore modification, indicating their contribution in the accumulation of faunal material, although the tooth marks frequencies are lower, as expected in assemblages mainly generated by humans.